KRITIK SASTRA FEMINIS DALAM PUPULAN CERPEN LUH JALIR KARYA MAS RUSCITA DEWI - Komang Puteri Yadnya Diari; Ni Luh Sukarmi Arianti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Kritik Satra Feminis Pupulan Cerpen Luh Jalir by Mas Ruscita Dewi aims to analyze gender issues in a short story collection book entitled Luh Jalir. The problems discussed are about gender stereotypes, violence, exploitation and the double burden of women which are the research studies of feminist literary criticism. This specific approach is used in an effort to reveal forms of gender injustice towards women. The method used in this research is qualitative which is described descriptively. The results of this study indicate the existence of gender stereotypes, violence, exploitation and the double burden of women in the short stories collection of Luh Jalir by Mas Ruscitadewi.Keyword: gender stereotype, violence, exploitation, double burden